Science, technology and society - Mosteiro, Arnaldo P. (Manila, Philippines : Educational Publishing House, 2004)
The aim of this books is to provide undergraduate students some background information on the nature, scope and limitation, and the importance of science and technology in society. Impart a broader view of the relationships among science, technology and society.
Chapter I. Introduction to science, technology and society -- Chapter II. The rise of concern over science and technology in society: Historical perspective -- Chapter III. Contemporary science and technology -- Chapter IV. Context of cience and technology -- Chapter V. The health status of Filipinos: a situationer.
Includes bibliographical references.
Keywords: SCIENCE -- TECHNOLOGY